DAB+ Testbed Erlangen - System Concept - Popp, Julian; Forster, Christian; Heuberger, Albert (Workshop on Digital Broadcasting, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.komele.dabtes
Keywords: Digital Broadcasting; DAB; Audio Coding

Energy Consumption of Low Data Rate M2M Communications in LTE - Popp, Julian; Robert, Jörg; Heuberger, Albert (Smart SysTech, 2015)
UnivIS-Import:2015-11-17:Pub.2015.tech.IE.komele.energy
Keywords: M2M; LTE; Energy Consumption; MTC; Protocol

Impact of Access Barring Schemes for Delay Tolerant MTC Devices on Energy Consumption - Popp, Julian; Robert, Joerg; Roth-Mandutz, Elke; Heuberger, Albert (IEEE Vehicular Technology Conference, 2022)
Cellular mobile communication systems have evolved from voice-centric to universal communication systems. After release 10 of the 3GPP standard, the group started working on specific enhancements tailored for machine-type communication (MTC), e.g. improving energy consumption, coverage enhancements and support for massive number of devices per cell. During the study for MTC enhancements, congestion on the random access channel was identified as a major issue in case a very high number of MTC devices tries to simultaneously access the cell. The existing access class barring (ACB) is a threshold based approach affecting all devices in a cell. Thus a new barring mechanism for latency-tolerant MTC devices was introduced: enhanced access barring (EAB). There have been numerous publications in the last years on how to optimize ACB and EAB for throughput and latency but only very few considered the major important impact on the overall energy consumption of the devices. Unlike previous publications, this paper investigates the effect of different access barring schemes on the energy consumption of MTC devices in case of high load on the random access channel and compares static and dynamic ACB settings as well as EAB-based solutions.
CRIS-Team Scopus Importer:2022-09-30
Keywords: 3GPP; 5G; ACB; Access Barring; Congestion Control; EAB; Energy Consumption; IoT; MTC

Recent Advances in Broadcast Audio Coding - Popp, Julian; Forster, Christian; Heuberger, Albert; et al. (IEEE BMSB 2013, 2013)
In the last decades there have been major advances in broadcasting technologies as well as a change in consumer behaviour and demands. The on-demand concepts and streaming technology, together with widely available fixed and mobile broadband Internet connections, had an eminent impact on the broadcasters to fit the consumer's needs with respect to content variety, quality and availability. Due to the limited capacity available for broadcasting content, especially over the air, more and more efficient codecs were necessary. This paper will give a short overview of the history of broadcast audio coding and point out which codecs are currently used in the major broadcasting systems, i.e. DVB, DAB and DRM. Recent developments in broadcast audio coding will be presented, focusing on spatial audio object coding and unified speech and audio coding technologies. © 2013 IEE
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.komele.recent
Keywords: Digital Broadcasting; Audio Coding; SAOC; xHE-AAC

Simulating MTC Data Transmission in LTE - Popp, Julian; Lex, Claudia; Robert, Jörg; Heuberger, Albert (Proceedings of the International Conference on Internet of things and Cloud Computing, 2017)
Keywords: ACM; ICC; IoT; LTE; Cloud Computing

Spurgenaue GPS Fahrzeuglokalisierung für moderne Fahrerassistenzsysteme durch die Übertragung von Korrekturdaten über Digitalradio (DAB) - Mickler, Florian; Robert, Jörg; Dietrich, Florian; Tollkühn, Andreas; Popp, Julian; Heuberger, Albert; Henkenhaf, Florian (17th International Congress Electronics in Vehicles (ELIV), 2015)